Síntese e análise estrutural de polímeros de coordenação e compostos moleculares derivados de Hg(TeAr)2 - Reckziegel, Poliana (2012)
This work presents a study related to the synthesis and structural analysis of coordination polymers and molecular compounds derived from Hg(TeAr)2. Was used as starting reagents some Hg(TeAr)2, considered basic building blocks for synthesis inorganic, and dithioligands of the type carbamate and phosphate, since they are extremely versatile in complexation to transition elements. The compounds obtained were: [Hg(TePh)(S2CNEt2)]n (1), [Hg(TePh){S2P(OEt)2}]n (2), [Hg(TePh)(S2CNC4H8)]n (3), [Hg2(Tedmb)2(S2CNC4H8)2]n (4), [Hg(dmb)(S2CNC4H8)] (5), [Hg(Temes)(S2CNC4H8)]n (6) e [Hg(mes)(S2CNC4H8)] (7), being can perform a structural study all these compounds, using as the main tool method the X-ray diffraction in sigle crystal, in addition to infrared spectroscopy and elementar analysis. Based on the structural analysis of these compounds can be concluded that the organization of crystal packing and the formation of supramolecular structures depends largely on the choice of appropriate ligands, being can thus control over the coupling between the minimum units generated, making possible to obtain systems really polymeric or molecular.